2019
DOI: 10.1039/c9ee00751b
|View full text |Cite
|
Sign up to set email alerts
|

An interface stabilized perovskite solar cell with high stabilized efficiency and low voltage loss

Abstract: Stabilization of the crystal phase of inorganic/organic lead halide perovskites is critical for their high performance optoelectronic devices. However, due to the highly ionic nature of perovskite crystals, even phase stabilized polycrystalline perovskites can undergo undesirable phase transitions when exposed to a destabilizing environment.While various surface passivating agents have been developed to improve the device performance of perovskite solar cells, conventional deposition methods using a protic pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
516
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 619 publications
(544 citation statements)
references
References 36 publications
15
516
0
1
Order By: Relevance
“…Sherkar et al showed that trap‐assisted recombination at the interface between HTL and the perovskite is the dominant loss mechanism 10. Thus, surface passivation of the perovskite is considered the most effective approach to suppress nonradiative recombination losses and, concomitantly, improve the photovoltage 11. Tavakoli et al showed that by surface passivation of the perovskite with adamantine amine a PCE of 20.93% can be achieved for mesoscopic PSCs 12.…”
Section: Photovoltaic Parameters Of Champion Devices With and Withoutmentioning
confidence: 99%
“…Sherkar et al showed that trap‐assisted recombination at the interface between HTL and the perovskite is the dominant loss mechanism 10. Thus, surface passivation of the perovskite is considered the most effective approach to suppress nonradiative recombination losses and, concomitantly, improve the photovoltage 11. Tavakoli et al showed that by surface passivation of the perovskite with adamantine amine a PCE of 20.93% can be achieved for mesoscopic PSCs 12.…”
Section: Photovoltaic Parameters Of Champion Devices With and Withoutmentioning
confidence: 99%
“…Much effort has thus been devoted to surface passivation by post‐depositing a solution of aliphatic or aromatic alkyl ammonium cations, thereby forming a thin layer of 2D perovskite like PEA 2 PbI 4 , [ 27 ] BA 2 PbI 4 , [ 28 ] AVAPbI 4 , [ 7,25 ] etc. [ 29,30 ] The superior stability of the 2D/3D structure PSCs was manifested by a recent encouraging work where a one‐year stable PSC with a 2D/3D heterostructure was reported. [ 7 ] Nevertheless, the commonly used two‐step procedure for preparation of 2D/3D heterostructures increases the complexity in device fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the ability to tune the fraction of 2D and 3D components on the surface and the bulk opens up these heterostructures for a range of device applications. Recently, it was reported that the surface passivation of bulk lead‐based 3D perovskite films with 2D molecules such as PEA through the post‐treatment processing of PEAI solutions can lead to extremely efficient and stable solar cells . In that system, the large‐bandgap 2D surface layer is sufficiently thin that charge injection to the contacts can still occur, though the layer still passivates trap states at the surfaces and grain boundaries of the 3D material.…”
mentioning
confidence: 99%